Education policy reform and the impact of free preschool education on boys’ and girls’ reading competence. - Ladrón de Guevara Rodríguez, Maria; López-Agudo, Luis Alejandro; Marcenaro-Gutiérrez, Óscar David (Wiley, 2023)
Numerous authors have reported a positive relationship between preschool enrolment and academic performance in later years, even helping to reduce the academic gap existing between students from different socio-economic backgrounds. In this context, this paper goes further by analysing the impact that early childhood education (from 3 to 6 years) has on Spanish boys’ and girls’ reading achievement when they are in fourth grade (10 years). For this purpose, we take advantage of the 2006 Spanish education reform that promoted free second stage preschool education by using data from Progress in International Reading Literacy Study 2011 and 2016 and an instrumental variable approach, in order to get closer to causality than previous literature for Spain. We find that attending preschool has a positive influence on reading achievement, well above the impact found when using simple ordinary least squares estimates, being higher for girls than for boys.
https://openpolicyfinder.jisc.ac.uk/id/publication/13988
Keywords: Educación - Modelos matemáticos; Política educativa; Lectura - Diferencias sexuales; Enseñanza preescolar; Policy reform; Gender; Preschool